2009
DOI: 10.1016/j.cell.2009.10.029
|View full text |Cite
|
Sign up to set email alerts
|

The Amygdala Is a Chemosensor that Detects Carbon Dioxide and Acidosis to Elicit Fear Behavior

Abstract: SUMMARY The amygdala processes and directs inputs and outputs that are key to fear behavior. However, whether it directly senses fear-evoking stimuli is unknown. Because the amygdala expresses acid sensing ion channel-1a (ASIC1a), and ASIC1a is required for normal fear responses, we hypothesized that the amygdala might detect a reduced pH. We found that inhaled CO2 reduced brain pH and evoked fear behavior in mice. Eliminating or inhibiting ASIC1a markedly impaired this activity, and localized ASIC1a expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
455
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(496 citation statements)
references
References 56 publications
31
455
3
3
Order By: Relevance
“…A bioinformatic search of the chromosome segment comprising the 17q11.2-q12 region suggested the ACCN1 gene as the most interesting gene, as the acid-sensing ion channels (ASICs) may be involved in anxiety-related pathways. [25][26][27] The ACCN1 gene comprises a genomic region of approximately 1. Figure 1 An overview of the study design: in stage 1, we conducted a genome-wide scan, which detected significant association between PD and a twomarker segment (D17S1294-D17S1293) on chromosome 17.…”
Section: Genotypingmentioning
confidence: 99%
“…A bioinformatic search of the chromosome segment comprising the 17q11.2-q12 region suggested the ACCN1 gene as the most interesting gene, as the acid-sensing ion channels (ASICs) may be involved in anxiety-related pathways. [25][26][27] The ACCN1 gene comprises a genomic region of approximately 1. Figure 1 An overview of the study design: in stage 1, we conducted a genome-wide scan, which detected significant association between PD and a twomarker segment (D17S1294-D17S1293) on chromosome 17.…”
Section: Genotypingmentioning
confidence: 99%
“…Functional MRI studies have shown that hypercapnia and hypoxia induced by brief apnea cause an increase in activity within the thalamus and cerebral cortex (23). There is recent evidence that acid sensing ion channels in the nucleus accumbens mediate a portion of the limbic response to hypercapnia (24), but the neurons and pathways responsible for the arousal response to hypercapnia have not been identified. Given the involvement of midbrain 5-HT neurons in sleep/wake regulation and their ability to sense pH changes, it has been proposed that midbrain 5-HT neurons initiate the arousal response to hypercapnia (11,13,25,26).…”
mentioning
confidence: 99%
“…One is to identify the physiological ligands. Wemmie and colleagues [78] demonstrated that ASIC1a in the amygdala is sufficient to detect CO 2 to elicit fear behavior. They also found that inhaled CO 2 reduces brain pH and evokes fearrelated behavior in mice, whereas eliminating or inhibiting ASIC1a markedly impairs this activity.…”
Section: Asics Acid-sensing Is Associated With Nociceptionmentioning
confidence: 99%
“…Blood CO 2 is converted into H + and HCO 3 -and detected by chemosensors in the nervous system. TASK1 channels in the brainstem [89] and ASIC1a in the amygdala [78] have been demonstrated to be important for CO 2 sensing. In addition, TRPA1 expressed in trigeminal neurons mediate CO 2 responses.…”
Section: Acid-sensing Receptors In Sensory System Sour Tastementioning
confidence: 99%